Political power and social theory. Vol. 21 - Go, Julian, 1970- (Political power and social theory,, 2010)
Political Power and Social Theory is an annual review, committed to advancing our interdisciplinary, critical understanding of the linkages between social relations, political power, and historical development. Alongside peer-reviewed chapters dealing with a diversity of topics, this volume contains a special section on the politics of the new middle class in the global south and post-socialist societies. Over the past few decades, globalization and urbanization have contributed to the development of a newly educated urban middle class around the world, but this new class has been rarely studied. Filling this void, the chapters in this section examine the middle classes in the developing world in areas as diverse as the Middle East, India, South Africa, the former Soviet Union, and Latin America. This is one of the only volumes examining the new urban middle classes in emerging economies. Exploring identity-formation, social change, urbanization and politics among the new middle class, the chapters together offer new insights on this understudied social group and raise provocative questions about politics and social change in the early 21st century around the globe.